Kazakh Ethnogenesis and The Formation of Turkic Identity in Central Asia: A Historical and Cultural Analysis - Arifeen Yama; Wasino (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: As a representative ethnos of the broader Turkic world in Central Asia, this study examines the historical development and modern identity of the Kazakh people. Tracing a trajectory from early Turkic empires and steppe nomadic traditions to the consolidation of the Kazakh Khanate and Soviet-era transformations, the research highlights the interplay of tribal genealogies, linguistic continuities, and Islamic influences particularly Sufi ethics in shaping Kazakh ethnogenesis. Drawing on historical texts, oral epics, and contemporary cultural practices, the paper positions Kazakhstan as both a historical heartland and a contemporary standard-bearer of Turkic civilisation. In the post-Soviet period, Kazakhstan has actively revitalized its Turkic and Islamic heritage through cultural diplomacy, digital platforms, and multilateral engagement with Turkic-speaking nations. The Kazakh identity, situated at the intersection of Kipchak ancestry, Sufi-Islamic tradition, and Eurasian geopolitics, demonstrates a dynamic continuity of Turkic civilisational identity through cultural memory, symbolic adaptation, and strategic reinvention. These findings not only deepen scholarly understanding of ethnogenesis and identity construction in Central Asia, but also underscore Kazakhstan’s evolving role in cultural diplomacy, heritage preservation, and regional nation-branding. Methodologically, this study demonstrates the value of integrating oral historiography with cultural diplomacy analysis in post-Soviet identity studies. The findings contribute to broader debates on post-Soviet nation-building, soft power strategy, and symbolic politics across the Turkic world. Abstrak: Sebagai etnis representatif dari dunia Turki yang lebih luas di Asia Tengah, studi ini menelaah perkembangan sejarah dan identitas modern bangsa Kazakh. Dengan menelusuri jalur dari kekaisaran awal Turki dan tradisi nomaden stepa hingga konsolidasi Kekhanan Kazakh dan transformasi era Soviet, penelitian ini menyoroti interaksi silsilah kesukuan, kesinambungan linguistik, dan pengaruh Islam—khususnya etika sufistik—dalam membentuk etnogenesis Kazakh. Berdasarkan teks sejarah, epos lisan, dan praktik budaya kontemporer, tulisan ini memposisikan Kazakhstan sebagai tanah air historis sekaligus pembawa standar peradaban Turki di era modern. Pada periode pasca-Soviet, Kazakhstan secara aktif merevitalisasi warisan Turki dan Islam melalui diplomasi budaya, platform digital, dan keterlibatan multilateral dengan negara-negara berbahasa Turki. Identitas Kazakh, yang berada di persimpangan antara leluhur Kipchak, tradisi Sufi-Islam, dan geopolitik Eurasia, memperlihatkan kesinambungan dinamis identitas peradaban Turki melalui memori budaya, adaptasi simbolik, dan reinvensi strategis. Temuan ini tidak hanya memperdalam pemahaman akademis tentang etnogenesis dan konstruksi identitas di Asia Tengah, tetapi juga menegaskan peran Kazakhstan yang terus berkembang dalam diplomasi budaya, pelestarian warisan, dan nation-branding regional. Secara metodologis, studi ini menunjukkan nilai integrasi historiografi lisan dengan analisis diplomasi budaya dalam kajian identitas pasca-Soviet. Hasil penelitian ini memberikan kontribusi pada perdebatan lebih luas tentang pembangunan bangsa pasca-Soviet, strategi soft power, dan politik simbolik di dunia Turki.